2001
DOI: 10.1523/jneurosci.21-19-07724.2001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Matrix Metalloproteinase-9 Gene Knock-Out on the Proteolysis of Blood–Brain Barrier and White Matter Components after Cerebral Ischemia

Abstract: Deleterious processes of extracellular proteolysis may contribute to the progression of tissue damage after acute brain injury. We recently showed that matrix metalloproteinase-9 (MMP-9) knock-out mice were protected against ischemic and traumatic brain injury. In this study, we examined the mechanisms involved by focusing on relevant MMP-9 substrates in blood-brain barrier, matrix, and white matter. MMP-9 knock-out and wild-type mice were subjected to transient focal ischemia. MMP-9 levels increased after isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

33
799
4
6

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 928 publications
(842 citation statements)
references
References 54 publications
33
799
4
6
Order By: Relevance
“…A hydroxymate MMP inhibitor, BB-1101, blocked the edema at 24 h and the early opening of the BBB at 3 h but failed to alter the secondary opening of the BBB at 48 h. Similar changes in MMPs have been seen in the mouse stroke model with reperfusion, using a more sensitive method of extraction of MMPs from small amounts of tissues (Gasche et al, 1999). A MMP-9 knockout mouse was found to have reduced infarct size and less BBB damage (Asahi et al, 2000(Asahi et al, , 2001. Mice that overexpress superoxide dismutase have reduced production of proMMP-9 (Gasche et al, 2001b).…”
Section: Role Of the Mmps In Neuroinflammation In Cerebral Ischemiamentioning
confidence: 88%
“…A hydroxymate MMP inhibitor, BB-1101, blocked the edema at 24 h and the early opening of the BBB at 3 h but failed to alter the secondary opening of the BBB at 48 h. Similar changes in MMPs have been seen in the mouse stroke model with reperfusion, using a more sensitive method of extraction of MMPs from small amounts of tissues (Gasche et al, 1999). A MMP-9 knockout mouse was found to have reduced infarct size and less BBB damage (Asahi et al, 2000(Asahi et al, , 2001. Mice that overexpress superoxide dismutase have reduced production of proMMP-9 (Gasche et al, 2001b).…”
Section: Role Of the Mmps In Neuroinflammation In Cerebral Ischemiamentioning
confidence: 88%
“…7,8 Although pharmacological or immunological inhibition of MMP9 has proven to be neuroprotective, as evidenced by a decreased infarct size, discrepant results have been reported in MMP9-deficient mice. 8,9,11 These discrepancies could be attributed to the use of different experimental models of cerebral ischemia (proximal and distal MCA occlusion in the presence or absence of reperfusion) and/or to the use of different techniques to assess the lesion extension (tissue staining for 2,3,5-triphenyl-tetrazolium-chloride). The present study includes the largest sample size of WT and MMP9/KO mice used to evaluate the infarct volume (n = 16 per group), and our results support the previous findings showing that MMP9 inhibition reduces the inflammatory response, blood-brain barrier disruption, and the development of edema after cerebral ischemia.…”
Section: Discussionmentioning
confidence: 99%
“…7 Experimental models of cerebral ischemia have proven that inhibiting MMPs can reduce the size of the ischemic lesion. 8 Published studies on MMP9-deficient mice have demonstrated the pivotal role of this protease in infarct expansion, 9,10 although the results remain controversial. 11 Our core hypothesis is that tissue MMP9 is a key protease required for an effective and successful cell-based therapy to potentiate vascular remodeling.…”
Section: Introductionmentioning
confidence: 99%
“…The same MMP can have different roles in different conditions. For example, MMP9 contributes to inflammation in mouse models of stroke, heart attack, Alzheimer's disease, some aspects of asthma and other lung inflammatory conditions, aortic aneurysms and autoimmune encephalomyelitis 9,[106][107][108][109][110] ; however, it functions as an anti-inflammatory agent in models of inflammatory skin and kidney diseases 89,111,112 . Current data indicate that MMP12 contributes to emphysema 113,114 , whereas MMP3 and MMP9 contribute to skin inflammatory conditions 89,115 .…”
Section: Mmps In Human Inflammatory Disease Modelsmentioning
confidence: 99%